Diabetic and idiopathic gastroparesis is associated with loss of CD206‐positive macrophages in the gastric antrum. Issue 6 (9th January 2017) - Grover, M.; Bernard, C. E.; Pasricha, P. J.; Parkman, H. P.; Gibbons, S. J.; Tonascia, J.; Koch, K. L.; McCallum, R. W.; Sarosiek, I.; Hasler, W. L.; Nguyen, L. A. B.; Abell, T. L.; et al.
Abstract: Background: Animal studies have increasingly highlighted the role of macrophages in the development of delayed gastric emptying. However, their role in the pathophysiology of human gastroparesis is unclear. Our aim was to determine changes in macrophages and other cell types in the gastric antrum muscularis propria of patients with diabetic and idiopathic gastroparesis. Methods: Full thickness gastric antrum biopsies were obtained from patients enrolled in the Gastroparesis Clinical Research Consortium (11 diabetic, 6 idiopathic) and 5 controls. Immunolabeling and quantitative assessment was done for interstitial cells of Cajal (ICC) (Kit), enteric nerves protein gene product 9.5, neuronal nitric oxide synthase, vasoactive intestinal peptide, substance P, tyrosine hydroxylase), overall immune cells (CD45) and anti‐inflammatory macrophages (CD206). Gastric emptying was assessed using nuclear medicine scintigraphy and symptom severity using the Gastroparesis Cardinal Symptom Index. Results: Both diabetic and idiopathic gastroparesis patients showed loss of ICC as compared to controls (Mean [standard error of mean]/hpf: diabetic, 2.28 [0.16]; idiopathic, 2.53 [0.47]; controls, 6.05 [0.62]; P =.004). Overall immune cell population (CD45) was unchanged but there was a loss of anti‐inflammatory macrophages (CD206) in circular muscle (diabetic, 3.87 [0.32]; idiopathic, 4.16 [0.52]; controls, 6.59 [1.09]; P =.04) and myenteric plexus (diabetic, 3.83 [0.27]; idiopathic, 3.59 [0.68]; controls, 7.46 [0.51]; P =.004). There was correlation between the number of ICC and CD206‐positive cells ( r =.55, P =.008). Enteric nerves (PGP9.5) were unchanged: diabetic, 33.64 (3.45); idiopathic, 41.26 (6.40); controls, 46.80 (6.04). Conclusion: Loss of antral CD206‐positive anti‐inflammatory macrophages is a key feature in human gastroparesis and it is associates with ICC loss. Abstract : Animal studies have highlighted an important role of macrophages in development of delayed gastric emptying. However, their role in human gastroparesis is unclear. Upon assessment of full thickness gastric antrum biopsies, both diabetic and idiopathic gastroparesis patients showed a loss of CD206‐positive anti‐inflammatory macrophages as compared to controls. This correlated with loss of ICC suggesting a role of innate immune cells in pathophysiology of human gastroparesis.